2010
DOI: 10.1186/1471-2458-10-234
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-sweetened carbonated beverage consumption correlates with BMI, waist circumference, and poor dietary choices in school children

Abstract: BackgroundThe prevalence of obesity and overweight is increasing globally. Frequently coexisting with under-nutrition in developing countries, obesity is a major contributor to chronic disease, and will become a serious healthcare burden especially in countries with a larger percentage of youthful population. 35% of the population of Saudi Arabia are under the age of 16, and adult dietary preferences are often established during early childhood years. Our objective was to examine the dietary habits in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
211
6
22

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(260 citation statements)
references
References 51 publications
21
211
6
22
Order By: Relevance
“…Snacking could contribute both to increased BMI and increased BP values. Prospective studies found a direct association between snacking and weight gain risk 24,46,47 . Moreover, high-sodium snacks are positively associated with the consumption of sugar-sweetened beverages that considerably increase the intake of carbohydrates and have been associated with children/adolescent obesity 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Snacking could contribute both to increased BMI and increased BP values. Prospective studies found a direct association between snacking and weight gain risk 24,46,47 . Moreover, high-sodium snacks are positively associated with the consumption of sugar-sweetened beverages that considerably increase the intake of carbohydrates and have been associated with children/adolescent obesity 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Omer et al [2] reported much higher rates of physical inactivity (91.7%) among schoolchildren. Collison et al [5] found that frequency of physical activity decreased as the age increases in both sexes. There are many reasons for high rate of physical inactivity, including dependence of children and adolescents on cars for daily activities, high rates of air pollution and high temperatures especially during summer times discourage performing outdoor activities.…”
Section: Discussionmentioning
confidence: 98%
“…Several research works showed that food habits are the most crucial factors affecting the health status of schoolchildren in KSA. For example, Collison et al [5] conducted a cohort study of 9433 schoolchildren aged 10 to 19 in the capital city (Riyadh).…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de muitos estudos não analisarem o consumo de sódio, estes observaram maior ingestão de alimentos industrializados entre os escolares do sexo masculino, apesar de ser elevado também entre as meninas (DALLA COSTA et al, 2007;COLLISON et al, 2010). Os alimentos industrializados possuem alto teor de sódio, gordura e açúcares simples, contribuindo para o maior teor de sódio na alimentação (SARNO et al, 2009).…”
Section: Componenteunclassified
“…Entre os meninos, DALLA COSTA et al (2007) Em estudo realizado com 9433 escolares da Arábia Saudita, observou-se maior consumo de açúcar e guloseimas entre os meninos, apesar das meninas também consumirem elevadas quantidades destes alimentos (COLLISON et al, 2010). No Brasil, o estudo de DALLA COSTA et al (2007) encontrou maior consumo de refrigerante, gorduras e óleos entre os meninos e maior consumo de açúcares e guloseimas entre as meninas.…”
Section: Introductionunclassified